The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1038/sj.eye.6702943
|View full text |Cite
|
Sign up to set email alerts
|

Performance of colour Doppler imaging discriminating normal tension glaucoma from healthy eyes

Abstract: Purpose Previous studies have shown decreased retrobulbar blood flow in normal tension glaucoma (NTG) compared to healthy controls. This study evaluates the ability of colour Doppler imaging (CDI) to identify patients with NTG. Methods Sixty-two patients with untreated NTG (mean age 57714 years) and 40 agematched controls (mean age 5879 years) were included in a prospective cross-sectional institutional study. Peak systolic velocity (PSV), end-diastolic velocity (EDV), and resistive indices (RI ¼ (PSV-EDV)/PSV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 33 publications
2
34
1
2
Order By: Relevance
“…The present study also found the RI of OA was negatively correlated with the MD values in the NTG and HTG patients; the RI of SPCA was negatively correlated with the MD values in the NTG and HTG patients; the RI of OA was positively correlated with the PSD value in the NTG and HTG patients. The PSV of control subjects in present study was higher as reported earlier [39][40][41], which may be contributed to ethnic differences between our study and the earlier reports.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…The present study also found the RI of OA was negatively correlated with the MD values in the NTG and HTG patients; the RI of SPCA was negatively correlated with the MD values in the NTG and HTG patients; the RI of OA was positively correlated with the PSD value in the NTG and HTG patients. The PSV of control subjects in present study was higher as reported earlier [39][40][41], which may be contributed to ethnic differences between our study and the earlier reports.…”
Section: Discussioncontrasting
confidence: 68%
“…The present study found that there was no significant difference in the latency and amplitude of P100 between NTG and HTG patients, which was contributed to that NTG and HTG may have the same pathogenesis of RGCs apoptosis and the similar character of retinal nerve fiber loss. Ocular hemodynamics had been shown to be a major factor in the pathogenesis of glaucomatous optic neuropathy [38,39]. Cellini et al [12] found that the patients with open angle glaucoma had the lower PSV and the higher RI of OA and SPCA comparing with that of normal subjects.…”
Section: Discussionmentioning
confidence: 98%
“…Thirty-two study cohorts from 21 studies provided sufficient information to be included in the multivariate analysis 17 19–21 32 37 39 41 42 48 49 52 53 61 62 64 65 69 76 80 81. Data for PSV in the OA failed Levene's test of equality, and the parameter was dropped from the model.…”
Section: Resultsmentioning
confidence: 99%
“…Bossuyt et al 8 reported that vascular dysregulation in NTG was not affected by the structure and function of the microcirculation or macrocirculation, including arterial stiffness, total peripheral resistance, cardiac output, and both peripheral and central hemodynamics. However, the studies conducted by Plange et al, 9 and Butt et al 10 were contradictory where they found significant association between ocular blood flow parameters and NTG.…”
Section: Ocular Blood Flow In Primary Open Angle Glaucoma and Normal mentioning
confidence: 93%